Decadal changes in common reef coral populations and their associations with algal symbionts (Symbiodinium spp.). (24th October 2014) - McClanahan, Timothy R.; Starger, Craig J.; Baker, Andrew C.
Abstract: Decadal populations changes in four coral taxa and their patterns of association with algal symbionts ( Symbiodinium spp. – 10 years of sampling) were examined on Kenyan back reefs over a period of climatic disturbances (1991−2009). Some of the better surviving taxa, Pavona and Pocillopora, were associated with variable temperature regimes and >50% of sampled colonies in these taxa had some of the more thermally tolerant Symbiodinium in clade D. In contrast, only around 35% of Acropora and no branching forms of Porites contained detectable levels of clade D, and both taxa experienced high levels of thermally‐induced mortality and poor recovery. Overall, however the relationship between Symbiodinium clade and population‐level success of coral hosts was not strong, and differential success inside and outside fisheries closures suggests that other factors, such as predation on corals, were also influential. Consequently, while Symbiodinium in clade D may contribute to the success of coral hosts across thermal disturbances, multiple ecological factors and additional biological traits also influence their long‐term survival.